Tracheostomy in Non-malignant Disorders (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Tracheostomy is a surgical procedure, often a life saving measure in a variety of clinical conditions. It is one of the commonest procedures carried out on the critically ill patient. The most common causes of non-malignant airway obstruction are head and severe facial trauma, cerebrovascular accident, coma, respiratory burn and presence of foreign bodies in airway etc. Tracheostomy is an increasingly utilised adjunct in the ICU management of patients. Effective tracheostomy management involved the multi-professional team in a coordinated approach.Objectives: To study the indications of tracheostomy in non-malignant disorders.Study design: Cross-sectional study.Study setting and period: Department of Otolaryngorhinology and Head- Neck surgery (Unit- 1,2,3), General Surgery, ICU, Casualty, Neurosurgery, Thoracic surgery, Burn & Plastic Surgery and relevant OPD in Dhaka Medical College Hospitalfrom6th September 2015 to 5th March 2016.Methods: A hospital based cross-sectional study. Fifty patients admitted to hospital, underwent tracheostomy for non-malignant factors. Purposive samplings technique was used. Detail demographic data were collected from the informant and recorded in structured case record form. Clinical examination and relevant investigation were done meticulously. All collected questionnaire checked very carefully to identify the error in the data. Data processing work consist of registration schedules, editing computerization, preparation of dummy table, analyzing and matching of data.Result: A total of 50 patients of non-malignant pathology causing airway patency loss in different ward unit of DMCH were selected. In this study, maximum numbers of patients (36%) were between 51-70 years age groups with mean age was 47.23±11.57 years. It was observed that, frequency of non-malignant aetiology for tracheostomy gradually increases with age. Study show that, 51-70 years was most frequent age group (36%). Out of 50 cases 82% were male. Present study show that socioeconomically majority patients were poor class (52%), highest percentage of patient comprised of day labourer (30%). Head trauma (12%) and cerebrovascular accidents (9%) were the most common etiological factor trauma was the major aetilogical group (50%),followed by, central drive problems or neurological disease (38%) and elective tracheostomy was done.Conclusion: Head and facial trauma, cerebrovascular accident, coma, respiratory burn and presence of foreign bodies etc. are common aetilogical factors. It was found that tracheostomy is safer alternative to intubation when a prolonged artificial airway is required.Bangladesh J Otorhinolaryngol 2022; 28(2): 157-164